2018
DOI: 10.1002/ange.201804602
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of Advanced Intermediates for Formal Total Syntheses of Tetrodotoxin

Abstract: Advanced intermediates for the syntheses of tetrodotoxin reported by the groups of Fukuyama, Alonso, and Sato were prepared. Key steps include the toluene dioxygenase mediated dihydroxylation of either iodobenzene or benzyl acetate. The resulting diene diols were transformed into Fukuyama's intermediate in six steps, into Alonso's intermediate in nine steps, and into Sato's intermediate in ten steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The chemoenzymatic syntheses of natural products, from cisdihydrodiol metabolites, have generally been restricted to those obtained from monocyclic arene substrates. [6][7][8][10][11][12][13][14][15][16][17][18][19] cis-Dihydrodiols of acridine and dictamnine, obtained by BPDO-catalyzed cis-dihydroxylation, were among the few examples of tricyclic arenes utilized in the chemoenzymatic synthesis of secondary metabolites. 20 Following on from the innovative use of a monocyclic arene cis-dihydrodiol of bromobenzene in chemoenzymatic syntheses, 6,7 this study has demonstrated that a tricyclic cis-dihydrodiol, formed by TDO-catalyzed cis-dihydroxylation of dibenzofuran, 27 can also be used as a precursor for the asymmetric synthesis of the chiral dibenzofuran derivatives, ribisins A and B.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The chemoenzymatic syntheses of natural products, from cisdihydrodiol metabolites, have generally been restricted to those obtained from monocyclic arene substrates. [6][7][8][10][11][12][13][14][15][16][17][18][19] cis-Dihydrodiols of acridine and dictamnine, obtained by BPDO-catalyzed cis-dihydroxylation, were among the few examples of tricyclic arenes utilized in the chemoenzymatic synthesis of secondary metabolites. 20 Following on from the innovative use of a monocyclic arene cis-dihydrodiol of bromobenzene in chemoenzymatic syntheses, 6,7 this study has demonstrated that a tricyclic cis-dihydrodiol, formed by TDO-catalyzed cis-dihydroxylation of dibenzofuran, 27 can also be used as a precursor for the asymmetric synthesis of the chiral dibenzofuran derivatives, ribisins A and B.…”
Section: Resultsmentioning
confidence: 99%
“…(3aR,4S,5S,10cR)-4-Methoxy-5-((4-methoxybenzyl)oxy)-2,2dimethyl-3a, 4,5,10c-tetrahydrobenzo[b] [1,3]dioxolo [4,5e]benzofuran (13). To a solution of alcohol 11 (16 mg, 0.040 mmol) in dry THF (4 mL) was added sodium hydride (5 mg), under an argon atmosphere, followed by the addition of methyl iodide (12 µL).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations